Psycho-social factors influencing negative body image in women - PORTNHAHINA, Mariia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. The development of body image is a complex process shaped by biological, psychological, and socio-cultural factors. In modern society, beauty standards promoted by the media, social networks, and the fashion industry greatly influence women's perceptions of their bodies. High levels of self-criticism and the pursuit of an ideal imposed by culture can lead to negative outcomes such as lower self-esteem, psychological distress, and eating disorders. The study aims is to identify the key psycho-social factors that contribute to negative body image in women and to explore how body image relates to self-esteem, psychological well-being, and stress levels.Methods. The study included 61 women aged 24 to 59. The methodology involved administering several instruments: Body Image Questionnaire (O. Skugarevsky, S. Sivuha), "Psychological Well-being Scale" by C. Ryff, Multifactor Personality Research Method (16 PF) by R. Cattell, Perceived Stress Scale (PSS-10); and a Self-assessment lifestyle questionnaire. Data processing was conducted using descriptive statistics, Spearman's correlation analysis (r), and regression analysis.Results. Findings showed that overall satisfaction with body image among participants was moderate. However, 26% of women displayed tendencies toward a negative body image. Correlation analysis indicated a positive relationship between body image and psychological well-being (r=0.225; p
Keywords: body image; women; psychological well-being; stress; self-esteem; value orientations; lifestyle